A Comparative Study of Hesse`s Siddhartha and the Historical Siddhartha - Chaudhary, Rajesh Kumar (Butwal Campus Journal, 2025)
In this paper, on the basis of Hesse's fictional Siddhartha and the historical Siddhartha Gautam, Herman Hesse's novel Siddhartha has been interpreted analyzing convergences and divergences between them rigorously. This paper satisfies the curiosity of understanding the novel comparing and contrasting various aspects of both the fictional and the historical characters. This paper has used primary as well as secondary sources to fulfil its queries and objective through interpretation of both the fictional and the historical characters analyzing qualitatively in descriptive form using the qualitative design and the comparative method. The analysis of the paper benefits the researchers for future research, for the writers to write novels with such existential theme and the readers to understand the subject matter of the novel comparatively through existential and intercultural philosophy.